2016
DOI: 10.1016/j.buildenv.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of personal exposures to carbon dioxide

Abstract: Elevated indoor CO2 levels are indicative of insufficient ventilation in occupied spaces and correlate with elevated concentrations of pollutants of indoor origin. Adverse health and wellbeing outcomes associated with elevated indoor CO2 levels are based on CO2 as a proxy, although some emerging evidence suggests CO2 itself may impact human cognition. Using portable monitors, we conducted an exposure study with 16 subjects in Singapore to understand the levels, dynamics and influencing factors of personal expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…The AC group who slept with air-conditioning operating tended to be exposed to lower air temperatures and relative humidities, but higher CO 2 levels than the NV group, since most of the participants spent 50% or more of their time at home. In addition, average daily CO 2 exposure for the AC group was substantially higher than the recorded median CO 2 mixing ratio during the experiment; the likely explanation is that the highest home CO 2 levels for the AC group occurred while sleeping [32]. Regarding acceptability responses, the MX group was observed to record higher TA and PAQA than the other two groups.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The AC group who slept with air-conditioning operating tended to be exposed to lower air temperatures and relative humidities, but higher CO 2 levels than the NV group, since most of the participants spent 50% or more of their time at home. In addition, average daily CO 2 exposure for the AC group was substantially higher than the recorded median CO 2 mixing ratio during the experiment; the likely explanation is that the highest home CO 2 levels for the AC group occurred while sleeping [32]. Regarding acceptability responses, the MX group was observed to record higher TA and PAQA than the other two groups.…”
Section: Discussionmentioning
confidence: 89%
“…The 90 th percentile level of CO 2 in transport environments is particularly striking; it is likely associated with a generally high occupant density especially during commute times on buses and in the rail mass rapid transit system (MRT). A detailed analysis of the CO 2 levels encountered and their potential significance has been reported by Gall et al [32]. Table 1 also summarizes the surveyed subjects' assessment of thermal and perceived air quality acceptable/unacceptable choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensor characteristics are reported in Table 3 , while a study summary is reported in the supplemental material (Tables S1 and S2) . Most of the selected papers were related to the monitoring of CO [ 5 , 6 , 9 , 29 , 31 , 36 , 38 , 39 ], CO 2 [ 5 , 9 , 29 , 40 , 41 , 42 , 43 , 44 ], O 3 [ 3 , 5 , 9 , 29 , 31 , 36 ] and NO 2 [ 6 , 9 , 29 , 31 , 38 ], even though other pollutants were sometimes considered, such as NO [ 5 , 6 , 29 ], SO 2 [ 29 , 38 ]; VOC [ 45 ], and hydrocarbons and acids [ 46 ]. Several studies reported results regarding wearable sensors provided to pedestrians.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of bedroom ventilation on overall exposure to CO 2 has been highlighted in some recent studies. The study by Gall et al assessed CO 2 exposure of participants over their entire day and found that occupants in bedrooms with split air conditioners (AC) faced greater mean daily integrated CO 2 exposures and frequency of exposure to critical levels of CO 2 , as compared to occupants in naturally ventilated (NV) bedrooms. In a similar study, it was found that bedrooms with natural ventilation provided better sleeping condition than those with split ACs, even though the thermal conditions of bedrooms with AC stayed within recommended limits while in NV bedrooms, the limits were routinely exceeded.…”
Section: Introductionmentioning
confidence: 99%